Mark Goodacre, Thomas and the Gospels. The Making of an Apocryphal Text (London: SPCK, 2012) - Oracz, Anna (The Biblical Annals, 2015)
Book review: Mark Goodacre, Thomas and the Gospels. The Making of an Apocryphal Text (London: SPCK, 2012). Pp. 226. £18.99. ISBN 9780281067763. Published in the USA as Thomas and the Gospels. The Case for Thomas’s Familiarity with the Synoptics (Grand Rapids, MI: Eerdmans, 2012). Pp. 236. 28.50. ISBN 9780802867483.